The Effects of Education, Motivation, and Inhaler Skills Program through Line Application on Clinical Control in Patients with Chronic Obstructive Pulmonary Disease - Tippala, Warunee; Wattanakitkrileart, Doungrut; Pongthavornkamol, Kanaungnit (Nursing Science Journal of Thailand, 2021)
Purpose: To study the effects of education, motivation, and inhaler skills program through line application on clinical control in patients with chronic obstructive pulmonary disease. Design: Experimental design. Methods: The total sample size was 63. There were 31 in the experimental group and 32 in the control group. The experimental group received standard nursing care and the education, motivation, and inhaler skills program through line application. The control group received standard nursing care and self-care guidebook. The duration of study was six weeks. The research outcomes were collected using the clinical COPD questionnaire. The data were analyzed using descriptive statistics, and t-test. Main findings: The results showed that the majority of participants (95.3%) were male with an average age of 72.14 years (SD = 9. 46). At post-intervention, the experimental group had significantly better clinical control than before receiving the program (p < .05) and better than the control group (p < .05). Conclusion and recommendations: The finding of this study confirms the effects of education, motivation, and inhaler skills program through line application to increase clinical control in patients with COPD. Nurses should use this program to promote accuracy in using inhaler medication and to provide knowledge in self-care for control of COPD in clinical practice, particularly during the scheduled appointment.